Pathway-Based Analysis Revealed the Role of Keap1-Nrf2 Pathway and PI3K-Akt Pathway in Chinese Esophageal Squamous Cell Carcinoma Patients With Definitive Chemoradiotherapy - Dai, Honghai; Wei, Yanjun; Liu, Yunxia; Liu, Jingwen; Yu, Ruoying; Zhang, Junli; Pang, Jiaohui; Shao, Yang; Li, Qiang; Yang, Zhe (Frontiers in Genetics, 2022)
Esophageal squamous cell carcinoma (ESCC) is the major type of EC in China. Chemoradiotherapy is a standard definitive treatment for early-stage EC and significantly improves local control and overall survival for late-stage patients. However, chemoradiotherapy resistance, which limits therapeutic efficacy and treatment-induced toxicity, is still a leading problem for treatment break. To optimize the selection of ESCC patients for chemoradiotherapy, we retrospectively analyzed the clinical features and genome landscape of a Chinese ESCC cohort of 58 patients. TP53 was the most frequent mutation gene, followed by NOTCH1. Frequently, copy number variants were found in MCL1 (24/58, 41.4%), FGF19 (23/58, 39.7%), CCND1 (22/58, 37.9%), and MYC (20/58, 34.5%). YAP1 and SOX2 amplifications were mutually exclusive in this cohort. Using univariate and multivariate analyses, the YAP1 variant and BRIP1 mutant were identified as adverse factors for OS. Patients with PI3K-Akt pathway alterations displayed longer PFS and OS than patients with an intact PI3K-Akt pathway. On the contrary, two patients with Keap1-Nrf2 pathway alterations displayed significantly shortened PFS and OS, which may be associated with dCRT resistance. Our data highlighted the prognostic value of aberrant cancer pathways in ESCC patients, which may provide guidance for better chemoradiotherapy management.